Significance and In Vivo Detection of Iron-Laden Microglia in White Matter Multiple Sclerosis Lesions - Gillen, Kelly M.; Mubarak, Mayyan; Nguyen, Thanh D.; Pitt, David (Frontiers in Immunology, 2018)
Microglia are resident immune cells that fulfill protective and homeostatic functions in the central nervous system (CNS) but may also promote neurotoxicity in the aged brain and in chronic disease. In multiple sclerosis (MS), an autoimmune demyelinating disease of the CNS, microglia and macrophages are involved in the development of white matter lesions and in disease progression, where microglia are chronically activated throughout the normal appearing white matter (NAWM). In this review, we discuss an additional compartment of myeloid cell activation in MS, i.e. the rim and normal adjacent white matter of chronic active lesions. In chronic active lesions, microglia and macrophages usually contain high amounts of iron, express markers of proinflammatory polarization, are activated for an extended period of time (years) and drive chronic tissue damage. Iron-positive myeloid cells can be visualized and quantified with quantitative susceptibility mapping (QSM), an MR imaging technique. Thus, QSM has potential as an in vivo biomarker for chronic inflammatory activity in established white matter MS lesions. Reducing chronic inflammation associated with iron accumulation using existing or novel MS therapies may impact disease severity and progression.